Current developments in the oral drug delivery of fucoidan - Tran, Phuong H.L.; Lee, Beom Jin; Tran, Thao T.D. (International Journal of Pharmaceutics, 2021)
Fucoidan is well known to have various biological functions and is often investigated for pharmaceutical applications. Several studies have been conducted on clinical applications of fucoidan in recent years, especially regarding its oral drug delivery. Although fucoidan has shown promising results in various dosage forms, its potential applications as a dietary supplement have been demonstrated, and recent studies show that oral administration of fucoidan is preferred. However, the focus on the oral delivery of fucoidan in recent studies has caused its potency in therapy to be understudied. This review aims to provide results on the promising fucoidan activity by oral administration with in vivo studies. In addition to using it as an active ingredient, the utilization of fucoidan as an excipient in oral drug delivery systems will be discussed. An overview of fucoidan administration by oral delivery in recent promising studies will provide a direction for further investigations in clinical applications, particularly for fucoidan, which has a broad spectrum of bioactive properties.
Keywords: Administration, Oral; Drug Delivery Systems; Excipients; Polysaccharides; Biological activities; Dosage form; Drug delivery; Nanocomplex; Oral fucoidan